2017
DOI: 10.1111/ijcp.12929
|View full text |Cite
|
Sign up to set email alerts
|

Coexistent malignant conditions in rheumatoid arthritis - A population-based cross-sectional study

Abstract: Rheumatoid arthritis is associated with several malignant disorders, in particular non-Hodgkin's lymphoma. Appropriate measures for non-Hodgkin's lymphoma screening in this patient population should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…The study has an observational design and not an interventional one, which is an inherent limitation to any cross‐sectional study of this type. Previous experience with the CHS population‐based study has indicated that the data are of high quality and that the associations that were detected were identical to those that were observed when smaller groups of patients with definite diagnoses were used . Our study revealed statistically significant difference towards medium (but not high) SES among RA patients as compared with controls, but the difference was small and without an overt clinical impact.…”
Section: Discussionsupporting
confidence: 79%
“…The study has an observational design and not an interventional one, which is an inherent limitation to any cross‐sectional study of this type. Previous experience with the CHS population‐based study has indicated that the data are of high quality and that the associations that were detected were identical to those that were observed when smaller groups of patients with definite diagnoses were used . Our study revealed statistically significant difference towards medium (but not high) SES among RA patients as compared with controls, but the difference was small and without an overt clinical impact.…”
Section: Discussionsupporting
confidence: 79%
“…The CHS database was originally created to accommodate data for clinical proposes, therefore, it was designed to act as a data registry according to diagnostic criteria of disorders but rather to code diseases according to the International Classification of Diseases (ICD) for statistical, economical and administrative purposes. However, the validity of the diagnoses as exhibited in previous studies have been shown to be high and reliable [ 8 , 9 , 20 24 ].…”
Section: Discussionmentioning
confidence: 91%
“…In this study, we presented the increased rate of cardiovascular risk factors among RA patients. In some previous reports, we have shown that those patients also tend to have higher rates of ischemic heart disease, gout, COPD, aortic aneurysms, malignancies (in particular non-Hodgkin’s lymphoma), and also psychiatric comorbidities such as bipolar and anxiety disorders [13, 23-25, 35-37]. …”
Section: Discussionmentioning
confidence: 99%
“…The validity of the diagnoses in the registry, which are based on hospital and primary care physicians and specialists’ reports, was found to be high in previous studies [21, 22]. Our group has recently published several papers investigating comorbidities among RA patients based on the CHS database using similar investigational methodology [13, 23-25]. Data withdrawn from the database represent a current situational analysis of co-existing variables and diagnoses without regard to chronology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation